Integrating the deductive method and holistic assessment approach to teaching English grammar in English education programmes - I Made Sujana; Udin Udin; Ni Wayan Mira Susanti; Arifuddin Arifuddin (Institut Agama Islam Negeri Palopo, 2020)
Mastery of English grammar for students in English education departments has a dual purpose, namely to improve their ability to communicate in English fluently and accurately, and to prepare them for becoming English teachers capable of explaining aspects of the English language. Thus, the English grammar course series is expected to equip students with the ability to use the language at the same time as explaining elements of the English language. This investigation aims to improve the learning, learning process, and the results of English grammar courses by integrating the deductive method and holistic assessment approach. This consists of assessment for learning (AfL), assessment as learning (AaL), and assessment of learning (AoL). The study was conducted among 72 fourth-semester students in the English education department at the University of Mataram. Data were collected using various techniques such as tests, observations, portfolios, and documentation, and were analysed qualitatively and quantitatively. From the analysis it was concluded that (1) the materials of EG were designed to fulfil the teaching and learning process by integrating the deductive method and the holistic assessment approach, with the proportion of AfL and AaL higher than that of AoL; (2) the integration produced a significant improvement in the TOEFL test (SWE section), with an increase of 63.24 points – from an average 388.84 on the pre-test to 452.01 on the post-test; (3) students responded positively to both the model used and the implementation of the deductive method and holistic assessment. The practical implication of this research is that those teaching grammar in English education need to consider applying holistic assessment in both design and implementation.